Exploring the link between internet addiction and aggression in Mysore's adolescents: a gender perspective - Mathew, Steven S.; Thomas, Alisha; Chakrashali, Sulochanadevi B. (International Journal Of Community Medicine And Public Health, 2024)
Background: Internet addiction has become a major concern affecting adolescents' personal, social, and academic lives. This study aimed to examine the relationship between internet addiction and aggression across genders, focusing on gender-specific patterns. Methods: The study included 480 adolescents from educational institutions in Mysore, Karnataka, selected through convenience sampling. Internet addiction was assessed using the Internet Addiction Test, while aggression patterns were evaluated using the validated Buss and Perry Aggression Questionnaire. Results: There were no significant differences in overall internet addiction and aggression levels between male and female adolescents, linear regression analysis indicated a stronger correlation between internet addiction and aggression in males (R = 0.350, p<0.01) compared to females (R = 0.213, p<0.01). Additionally, binary logistic regression showed that verbal aggression was significantly associated with internet addiction (p = 0.003, Exp(B) = 1.105), particularly in females. Conclusions: The findings suggest that, although male and female adolescents exhibit similar levels of internet addiction and aggression, it can be observed that males show slightly higher levels of internet addiction and aggression, it is shown that internet addiction is a stronger predictor of aggression in males and that females have higher aggression levels regardless of their internet addiction usage. It was also found that verbal aggression is notably associated with higher internet use. These insights underscore the importance of gender-specific interventions aimed at managing problematic internet use and mitigating its influence on aggressive behaviors in adolescence.